2017
DOI: 10.5606/kbbihtisas.2017.03366
|View full text |Cite
|
Sign up to set email alerts
|

Post-tonsillectomy bleeding: Our 10-year experience

Abstract: ÖZAmaç: Bu çalışmada, tonsillektomi sonrası kanama ile başvurup tedavileri yapılmış hastaların özellikleri değerlendirildi ve ilişkili risk faktörleri araştırıldı. Hastalar ve Yöntemler:Ocak 2005 -Aralık 2015 tarihleri arasında tonsillektomi/adenotonsillektomi sonrası tonsil lojundan kanama yakınmasıyla kliniğimize başvuran ve tedavi edilen toplam 40 hasta (19 erkek, 21 kadın; ort. yaş 18.2 yıl; dağılım 2-48 yıl) çalışmaya alındı. Tonsillektomi sonrası kanama yaş, cinsiyet, tonsillektomi endikasyonu ve yöntemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
(94 reference statements)
0
2
0
2
Order By: Relevance
“…13,29 Çakır et al, in their study with a sample of 40 patients, reported that secondary hemorrhage was more common in patients with PTH. 9 Likewise, in the study performed by Yorgancılar et al on 23 patients, it was concluded that 4 patients had primary hemorrhage and 19 patients had secondary hemorrhage. In this meta-analy-sis study, it was found that the risk of secondary hemorrhage was higher than primary hemorrhage.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…13,29 Çakır et al, in their study with a sample of 40 patients, reported that secondary hemorrhage was more common in patients with PTH. 9 Likewise, in the study performed by Yorgancılar et al on 23 patients, it was concluded that 4 patients had primary hemorrhage and 19 patients had secondary hemorrhage. In this meta-analy-sis study, it was found that the risk of secondary hemorrhage was higher than primary hemorrhage.…”
Section: Discussionmentioning
confidence: 95%
“…7,8 In addition, secondary hemorrhage is less common and more frightening. 1,[8][9][10][11] The variables affecting PTH are listed as follows: preoperative factors [patient's gender, age, indication for surgery, hematological parameters, physiological oropharyngeal bacterial colonization, genetic disorders affecting the coagulation mechanism, hemorrhage diathesis (susceptibility), use of anticoagulant or antiplatelet medications, lupus, kidney or liver failure, the presence of diseases that can cause hemorrhage such as hypothyroidism, recent viral infections], perioperative factors (surgical technique, experience of the surgeon performing the surgery, intraoperative medicine used including anesthetic agents and steroids, blood loss during the operation, the season and ambient temperature of the operation), postoperative factors (postoperative pain and analgesic control, antimicrobial treatment, time after the operation, postoperative blood pressure, insufficient fluid intake, postoperative saliva content change). 6,8,[10][11][12][13][14] For example, children with tonsillectomy due to chronic tonsillitis have more scars on their tonsils and surrounding tissue, and the tonsils are more difficult to remove.…”
mentioning
confidence: 99%
“…Tonsillektomi sonrası görülebilen komplikasyonlar arasında ağrı, tonsil lojunda kanama, havayolu obstrüksiyonu, dehidratasyon ve pulmoner ödem gibi durumlar vardır. Posttonsillektomi kanama (PTK) nadir fakat hayatı tehdit edebileceği için oldukça önemli bir komplikasyondur (1). PTK tonsillektomi sonrası en korkulan komplikasyondur.…”
Section: Introductionunclassified
“…3 Yapılan çalışmalarda, ikincil kanamaların daha çok 5-12. günlerde geliştiği ve 60. güne kadar gelişebileceği vurgulanmaktadır. 8,9 Çalışmamızda ise ortalama kanama zamanı 7,6 gün ve en geç kanama 16. günde idi. Birincil kanamalar sıklıkla cerrahi teknikle ilgili olarak ortaya çıkmakta iken, ikincil kanamalardan daha çok tonsillektomi sahasında ortaya çıkan enfeksiyonlar ve rezidüel tonsil dokusu sorumlu tutulmaktadır.…”
unclassified